Factual Actions as Objects of State Administrative Disputes in State Administrative Courts Following the Issuance of the Job Creation Law - Cahyandari, Dewi; Ayub, Zainal Amin; Pratama, Luvieandra; Sudjati, Xaviera Qatrunnada Djana (Universitas Brawijaya, 2024)
The State Administrative Court Law currently in force presents contradictions, given that administrative activities represent one of its objects, which are inherently dynamic. This raises a significant question about whether the State Administrative Court Law, enacted in 1986, can still uphold its substantive principles. This study focuses on the discussion of factual actions. The Job Creation Law subsequently removed the determination of fictitious positive cases from the jurisdiction of the State Administrative Court. This study aims to describe, analyze, and disclose the fundamental meaning of factual actions as the objects of administrative disputes in the State Administrative Court. The study employs a normative method with legislative and philosophical approaches. The interpretation of factual actions as objects of administrative disputes in the State Administrative Court, following the issuance of Government Regulation in Lieu of Law No. 2 of 2022, requires that a request to a government official or body not addressed within the stipulated time frame is legally considered de facto granted. It is essential to consider the reality in the field, recognizing that the role of the State Administrative Court remains necessary to ensure legal certainty and protection for individuals or legal entities (Indonesian citizens) who submit requests for decisions to government officials or bodies.